Antinutritional Content, Flour Characteristics, and Protein Profiles of Taro Tubers (Colocasia esculenta) by Fermentation with Lactobacillus plantarum - Maria Natalia Wewo; Sasangka Prasetyawan; Arie Srihardyastutie (Chemistry Department, The University of Brawijaya, 2018)
The purpose of this research was studying the optimum condition, the change of oxalate content, the characteristic of flour, and protein profile of taro tuber that fermented with Lactobacillus plantarum. The optimum condition of fermentation was determined based on the lowest oxalate content in flour. The optimum conditions of fermentation studied were variation of pH (4-6), temperature (30⁰–50 ⁰C) and incubation time (6–48 hours). The result showed that the optimum condition of fermentation was achieved at pH 5, 35 °C in 48 h incubation time. The fermented taro flour characteristics were the increasing level of starch (4.76%), amylose (0.43%). amylopectin (4.36%) and protein (0.99%). The fermented taro protein profiles showed that the allergenic proteins were not present, suggesting those proteins were missing due to fermentation process.